2009
DOI: 10.3748/wjg.15.4028
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus subgenotypes and basal core promoter mutations in Indonesia

Abstract: AIM:To identify the distribution of hepatitis B virus (HBV) subgenotype and basal core promoter (BCP) mutations among patients with HBV-associated liver disease in Indonesia. METHODS:Patients with chronic hepatitis (CH, n = 61), liver cirrhosis (LC, n = 62), and hepatocellular carcinoma (HCC, n = 48) were included in this study.HBV subgenotype was identified based on S or preS gene sequence, and mutations in the HBx gene including the overlapping BCP region were examined by direct sequencing. RESULTS:HBV genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…HBV/C1 was commonly found in Southeast Asia (the western part of Indonesia, Malaysia, Thailand, Vietnam and Bangladesh) and Southern China [12,13,20,21,27]. The Malay populations in the western (Melayu Minangkabau) and southern parts (Melayu Jawa and Melayu Bugis) of the Peninsular Malaysia were believed to have had more historical and cultural links with the populations from the Indonesian archipelago [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HBV/C1 was commonly found in Southeast Asia (the western part of Indonesia, Malaysia, Thailand, Vietnam and Bangladesh) and Southern China [12,13,20,21,27]. The Malay populations in the western (Melayu Minangkabau) and southern parts (Melayu Jawa and Melayu Bugis) of the Peninsular Malaysia were believed to have had more historical and cultural links with the populations from the Indonesian archipelago [28].…”
Section: Discussionmentioning
confidence: 99%
“…They originated from and still mainly reside in the West Sumatra province of Sumatra Island [17]. Previous studies have shown that HBV genotype C is the most prevalent among HBV carriers in this population, which is different from other populations in Sumatra Island [12-14]. However, the numbers of subjects in these studies were low.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the Indonesian viruses, some mutations in the HBV genome that are associated with severe liver disease have been reported, including mutations in the basal core promoter region (e.g., A1762T/G1764A and T1753V) (19)(20)(21) and the pre-S region (22,23). Several minor drug-resistant mutations of HBV in Indonesian treatment-naive patients with chronic hepatitis were recently detected using a deep sequencing method (24).…”
mentioning
confidence: 99%